Cis-epistasis at the LPA locus and risk of cardiovascular diseases. Issue 4 (20th April 2021) - Zeng, Lingyao; Moser, Sylvain; Mirza-Schreiber, Nazanin; Lamina, Claudia; Coassin, Stefan; Nelson, Christopher P; Annilo, Tarmo; Franzén, Oscar; Kleber, Marcus E; Mack, Salome; Andlauer, Till F M; Jiang, Beibei; et al.
Abstract: Aims: Coronary artery disease (CAD) has a strong genetic predisposition. However, despite substantial discoveries made by genome-wide association studies (GWAS), a large proportion of heritability awaits identification. Non-additive genetic effects might be responsible for part of the unaccounted genetic variance. Here, we attempted a proof-of-concept study to identify non-additive genetic effects, namely epistatic interactions, associated with CAD. Methods and results: We tested for epistatic interactions in 10 CAD case–control studies and UK Biobank with focus on 8068 SNPs at 56 loci with known associations with CAD risk. We identified a SNP pair located in cis at the LPA locus, rs1800769 and rs9458001, to be jointly associated with risk for CAD [odds ratio (OR) = 1.37, P = 1.07 × 10 −11 ], peripheral arterial disease (OR = 1.22, P = 2.32 × 10 −4 ), aortic stenosis (OR = 1.47, P = 6.95 × 10 −7 ), hepatic lipoprotein(a) (Lp(a)) transcript levels (beta = 0.39, P = 1.41 × 10 −8 ), and Lp(a) serum levels (beta = 0.58, P = 8.7 × 10 −32 ), while individual SNPs displayed no association. Further exploration of the LPA locus revealed a strong dependency of these associations on a rare variant, rs140570886, that was previously associated with Lp(a) levels. We confirmed increased CAD risk for heterozygous (relative OR = 1.46, P = 9.97 × 10 −32 ) and individuals homozygous for the minor allele (relative OR = 1.77, P = 0.09) of rs140570886. Using forward model selection, we also show that epistatic interactions between rs140570886, rs9458001, and rs1800769 modulate the effects of the rs140570886 risk allele. Conclusions: These results demonstrate the feasibility of a large-scale knowledge-based epistasis scan and provide rare evidence of an epistatic interaction in a complex human disease. We were directed to a variant (rs140570886) influencing risk through additive genetic as well as epistatic effects. In summary, this study provides deeper insights into the genetic architecture of a locus important for cardiovascular diseases. Graphical Abstract: